Local delivery of 17β-estradiol improves reendothelialization and decreases inflammation after coronary stenting in a porcine model - Chandrasekar, Baskaran; Sirois, Martin G.; Geoffroy, Pascale; Lauzier, Dominique; Nattel, Stanley; Tanguay, Jean-François (Thrombosis and Haemostasis, 2005)
In the current study, we investigated the effect of local intravascular delivery of 17β-estradiol (17β-E) on subsequent instent neointimal hyperplasia. Twenty-seven stents were implanted in coronary arteries of juvenile swine. Coronary arteries were randomized to local treatment with 17β-E or no drug therapy (control-vehicle treated). Twenty-eight days posttreatment, angiographic images revealed an improved minimal lumen diameter (2.2 ± 0.2 vs. 1.3 ± 0.2 mm, P < 0.005) and a reduction of late lumen loss (1.7 ± 0.2 vs. 2.3 ± 0.1 mm, P < 0.01) in 17β-E-treated vessels compared to control-vehicle treated. Histological analyses showed a reduction of stenosis (51.49 ± 6.75 vs.70.86 ± 6.24%, P < 0.05), mean neointimal thickness (0.51 ± 0.07 vs.0.83 ± 0.14 mm, P < 0.05) and inflammation score (1.29 ± 0.28 vs. 2.85 ± 0.40, P < 0.05) in 17β-E-treated arteries compared to control-vehicle treated arteries. Immunohistochemistry analyses revealed a reduction of proliferating smooth muscle cells and increased in-stent reendothelialization in 17β-E-treated arteries. Finally, we observed a correlation between neointimal hyperplasia and inflammation score, which in turn, was inversely related to reendothelialization. Locally delivered, 17β-E is inhibiting the inflammatory response and smooth muscle cells proliferation and improving vascular reendothelialization which together are contributing to reduce instent restenosis in a porcine coronary injury model. Together, these data demonstrate the potential clinical application of 17β-estradiol to improve vascular healing and prevent in-stent restenosis.
Keywords: Coronary disease; hormones; inflammation; restenosis; stents